A Companion to Media Authorship. - Gray, Jonathan (Wiley, 2013)
A Companion to Media Authorship offers 28 groundbreaking chapters which investigate the practices, attributions, and meanings of authorship. Revitalizing the study within media and cultural studies, this diverse and global collection provides the definitive work on the subject. Rethinks cultures of authorship and challenges the concept of auteurism across multiple media formsMoves beyond notions of the individual to focus on how authorship is collaborative, contested, and networked, examining cultures of authorship and the practicalities of how it worksDr.